DESIGN PLANNING WASTEWATER TREATMENT PLANT OF NATA DE COCO INDUSTRY WITH THE ACTIVATED SLUDGE PROCESS - Dinda Rita K. Hartaja; Imam Setiadi (BPPT, 2016)
Generally, wastewater of nata de coco industry contains suspended solids and COD were high, ranging from 90,000 mg / l. The high level of of the wastewater pollutants, resulting in nata de coco industry can not be directly disposed of its wastewater into the environment agency. Appropriate technology required in order to process the waste water so that the treated water can meet the environmental quality standards that are allowed. Designing the waste water treatment plant that is suitable and efficient for treating industrial wastewater nata de coco is the activated sludge process. Wastewater treatment using activated sludge process of conventional (standard) generally consists of initial sedimentation, aeration and final sedimentation.Keywords : Activated Sludge, Design, IPAL